Upaya Pemberdayaan Ekonomi Kreatif Melalui Pelatihan Buket di Desa Montongsari - Rizqi Aulia Putri; Jundy Yanuar Ramadhoni; Nurul Hidayah; Septi Alawiyah; Jasmine Ramadhani; Ulin Nihayah (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses creative economic empowerment efforts through bouquet-making training in Montongsari Village. The main focus of this study is to evaluate the impact of the training on improving the skills and income of the village community. Creative economic empowerment can develop the community's skills and resources needed to create income and manage their own businesses. It aims to reduce dependence on external assistance and increase economic stability. This research uses a Participatory Action Research (PAR) approach to evaluate the butterfly bouquet-making training that was conducted on July 12, 2024 in Montongsari Village. The training involved PKK mothers from various hamlets and aimed to increase the creative economic empowerment of the community. By using simple materials and involving participants in every stage of making, the training succeeded in improving their practical skills as well as their creativity. The results showed that participants were able to make high-quality bouquets and felt more confident to explore new business opportunities. The program also contributed to local economic development and supported Montongsari Village as a tourist village. This training proved the effectiveness of PAR in empowering communities in a practical and participatory manner